A influência da representatividade do epitélio glandular sobre a detecção de lesões precursoras do câncer cervical - COSTA, Dicleidson Luiz da Silva (2023)
The presence of Glandular and/or Metaplastic Cells in the Pap smear is considered a quality factor for the sample by the Ministry of Health (2016), on the other hand, the absence of any of these significantly increases the chances of generating false-negative results. Since, in 80% of cases, pre-malignant and malignant lesions are triggered in immature metaplastic cells that constitute the Squamocolumnar Junction (SJC) region. OBJECTIVE: To carry out an investigation into the relationship between the representativeness of Glandular/Metaplastic Epithelium and the number of positive tests for precursor alterations of Cervical Cancer in the Oncotic Colpocytology exams collected in the Health Units referenced in the city of Belém -PA, in the period from January 2018 to December 2021. METHODOLOGY: Descriptive, analytical, ecological study, with a quantitative approach, aimed at investigating the relationship between the representativeness of Glandular/Metaplastic Epithelium and the number of positive tests for precursor alterations of Cervical Cancer Uterus in the Oncotic Colpocytology exams collected in the Health Units referenced in the city of Belém-PA from January 2018 to December 2021, whose data were duly recorded on the DATASUS and SISCAN/SISCOLO Platforms. RESULTS: The frequency of representativeness of Squamous, Glandular and/or Metaplastic Epithelia and of the Transformation Zone was observed according to the year of examination. The distribution of Glandular Representativeness was as follows: 2018 - 69.93%, 2019 - 72.12%, 2020 - 65.02% and 2021- 62.96%, of PCCUs with detection of the presence of Endocervical Cells. In turn, the existence of ZT elements in the total sample of tests was as follows: 2018 - 71.92%, 2019 - 78.11%, 2020 - 74.47% and 2021 - 71.61%, with an average of presence period in 74.31% of the slides. Of the 119,610 Oncotic Colpocytology performed in that period, 11,044 (9.23%) reports showed alterations consistent with precursor lesions of the CCU. Of these, 9667 (87.5%) had characteristic epithelium of the Endocervical Canal, so that 1377 (12.5%) were constituted only by Squamous Epithelium. CONCLUSION: The performance of screening for pre-malignant and malignant lesions for cervical cancer, on a large scale in the population, through the Oncotic Colpocytology exam is an imperative component in the fight against Cervical Cancer. Therefore, the awareness of the target population, associated with the improvement of collection points for the Cervical Cancer Preventive Examination and the qualification of the Primary Care health teams are of paramount importance.